“How to Recognize if Your Child Is Seriously Ill” During COVID-19 Lockdown: An Evaluation of Parents' Confidence and Health-Seeking Behaviors - Lim, Emma; Mistry, Ravi D.; Battersby, Alexandra; Dockerty, Kerry; Koshy, Aaron; Chopra, Michelle N.; Carey, Matthew C.; Latour, Jos M. (Frontiers in Pediatrics, 2020)
Background: Parents' health-seeking behaviors has changed during the COVID-19 pandemic. Providing parents with guidance in decision making might improve their confidence to seek timely advice when a child becomes ill. The aim of this study was to evaluate the “How to recognize if your child is seriously ill” leaflet on parents' confidence, health-seeking behaviors, and usefulness during the COVID-19 lockdown. Method: A nine-item survey, codesigned with parent advisors, was used to measure confidence and health-seeking behavior. Social media was used for data collection in a 6-week period (April–June 2020) during COVID-19 lockdown in the United Kingdom. Categorical data were analyzed as frequencies, and inductive content analysis was performed with the qualitative data. Results: In total, 171 parents responded. Most parents (n = 160, 93.6%) found the leaflet helpful. The leaflet increased the confidence among 116 parents (67.8%) to recognize if their child is ill, and 156 (91.2%) parents had a better understanding of when and where to seek help. Thirty-three (19.2%) parents used the leaflet, while their child was unwell during COVID-19 lockdown, and in 14 (42%) cases, the leaflet resulted in changing health-seeking behavior for that episode. Twelve of these parents decided to seek medical consultation when they had not planned to before. Content analysis revealed three categories. (1) Knowledge—parents found the leaflet an objective source to validate their concerns. (2) Usability—parents reported that the leaflet was clearly designed. (3) Decision aid—parents commented that the leaflet provided clarification around recognition of serious symptoms and when and where to seek appropriate care. Conclusions: Our leaflet provided parents with guidance on decision making and risk assessment of ill children during COVID-19 lockdown. Parents found it helpful; it increased their confidence and positively changed their health-seeking behaviors. Providing parents with targeted information to recognize serious illness in children at home could potentially foster self-care and safely maintain a reduction in pediatric emergency attendances for self-limiting illnesses.